Fiscal administration - Mikesell, John L. (California, 1991)
Fiscal administration shows you how public budgets operate and lets you crunch the numbers yourself. And with the latest data from the US federal budget, including its breakdown, you can see for yourself how policymakers allocate money.
Keywords: "Finance, Public"